THE EFFECT OF DHUHA PRAYER HABITUATION ON STUDENT DISCIPLINE (STUDY AT MUHAMMADIYAH 2 SURAKARTA SENIOR HIGHSCHOOL) - Nareswari, Ardha Zahro; Chusniatun, C (Proceeding of International Conference of Islamic Education, 2024)
Discipline is one of the keys to success to be able to do the job correctly and on time. One of the characters that must be instilled in students from an early age is discipline. This is because students also have the role of children when at home, surrounded by rules that must be followed. The purpose of instilling this discipline is to instill compliance and compliance with applicable regulations. At SMA Muhammadiyah 2 Surakarta there is a program to habituate congregational dhuha prayer with the aim of training students to learn discipline and time management, this program is carried out for students of grades X, XI, XII, teachers and staff employees at school. The methods used in this study are observation, interviews, and documentation. The result of this study is that the habituation of dhuha prayers for students is carried out well, so as to increase student discipline and can prevent and change themselves from things that are not good.